Knowledge, beliefs and adherence to antimalarial medications among patients in the Ga East Municipality of Ghana - Amoako, Michelle Akua; Wutor, Victor Collins; N’guessan, Benoit Banga (Frontiers in Malaria, 2025)
Treatment adherence is necessary for several reasons, including preventing the development of resistance and avoiding progression to a severe form of the disease. This study explored patients’ beliefs and their impact on adherence to antimalarial medications (orthodox and herbal medicines). A cross-sectional survey was conducted over three weeks in the Ga East Municipal District of Ghana. The study involved 346 participants and employed comprehensive questionnaires to gather data, which was analyzed using STATA version 14. Despite the high prevalence of malaria in the district, adherence to antimalarial medication remained a challenge. The study revealed varying opinions among participants regarding the safety and efficacy of different antimalarial treatments. The research highlighted the connection between patients’ beliefs, age, knowledge, and adherence. Younger individuals showed higher adherence rates, emphasizing the need for age-specific interventions. Comprehensive knowledge also correlated with better adherence, highlighting the role of education. The study recommended the development of tailored educational campaigns that address misconceptions and foster trust between healthcare providers and patients. Innovative interventions, such as mobile phone-based reminders and incentives, were suggested to improve adherence. The research emphasized the importance of holistic malaria prevention strategies, including robust educational initiatives, targeted interventions in hotspot districts, and widespread distribution of insecticide-treated nets. The study’s insights offer actionable recommendations to enhance malaria control efforts in the Ga East Municipal District and beyond.